2000
DOI: 10.1016/s0022-2275(20)32071-x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of dopamine neurotransmission in the nucleus accumbens of rats deficient in n–3 polyunsaturated fatty acids

Abstract: We studied the effects of a diet chronically deficient in ␣ -linolenic acid, the precursor of long-chain n-3 polyunsaturated fatty acids, on dopaminergic neurotransmission in the shell region of the nucleus accumbens of rats. In vivo microdialysis experiments showed increased basal levels of dopamine and decreased basal levels of metabolites, 3,4-dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA), in awake rats from the deficient group compared to controls. The release of dopamine under KCl stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(12 citation statements)
references
References 40 publications
4
7
0
1
Order By: Relevance
“…The decrease in ventral striatal DA corresponds well with previous results showing that amphetamine and tyramine have reduced DA-releasing capability in the nucleus accumbens of n-3-def rats (Zimmer et al, 2000(Zimmer et al, , 2002. The blunted effects of amphetamine and tyramine are probably related to reductions in the number of vesicular monoamine transporters in deficient rats, which lead to depletion of vesicular DA available for release (Chalon, 2006;Zimmer et al, 2000Zimmer et al, , 2002. However, Zimmer et al (2000) reported a paradoxical elevation of basal DA levels in microdialysis samples collected from the nucleus accumbens shell of awake n-3-def rats.…”
Section: Discussionsupporting
confidence: 91%
“…The decrease in ventral striatal DA corresponds well with previous results showing that amphetamine and tyramine have reduced DA-releasing capability in the nucleus accumbens of n-3-def rats (Zimmer et al, 2000(Zimmer et al, , 2002. The blunted effects of amphetamine and tyramine are probably related to reductions in the number of vesicular monoamine transporters in deficient rats, which lead to depletion of vesicular DA available for release (Chalon, 2006;Zimmer et al, 2000Zimmer et al, , 2002. However, Zimmer et al (2000) reported a paradoxical elevation of basal DA levels in microdialysis samples collected from the nucleus accumbens shell of awake n-3-def rats.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the FFAs-FFAR1 system was suggested to play an important role in striatal DA and 5-HT effluxes. In fact, previous studies using animals deficient in n-3 polyunsaturated FFAs reported that the deficiency enhanced anxiety-like behaviors in mice ( Harauma and Moriguchi, 2011 ) and modified striatal DA availability or basal DA release in rats ( Zimmer et al, 2000 ; Bondi et al, 2014 ), which may be at least partly consistent with both our previous ( Aizawa et al, 2019 ) and present data. Conversely, n-3 FFAs, such as eicosapentaenoic acid and docosahexaenoic acid, were suggested to reduce stress and anxiety-like behaviors in animal studies ( Song et al, 2007 ; Aizawa et al, 2019 ), and supplementation of n-3 FFAs reduced the risk of progression to psychotic disorder and psychiatric morbidity ( Amminger et al, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…EFAs have been shown to influence the regulation of metabolism of dopamine. In rats having the diet poor in fatty acids ω-3, the increase in the concentration of dopamine and decrease in the concentration of its metabolites in the nucleus accumbens was observed, compared with the diet with optimal fatty acid content [62]. In turn, in the frontal cortex, the decrease in concentration was observed.…”
Section: The Role Of Efas In the Functioning Of Cnsmentioning
confidence: 90%
“…U szczurów karmionych dietą deficytową w kwasy ω-3 obserwowano wzrost stężenia dopaminy oraz spadek stężenia jej metabolitów w jądrze półleżącym w porównaniu z dietą o optymalnej zawartości kwasów tłuszczowych [62]. W korze czołowej obserwowano z kolei spadek stężenia.…”
Section: Rola Nnkt W Funkcjonowaniu Oununclassified